2020
DOI: 10.3390/ani10081431
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane and Carbon Dioxide Elicit Similar Behavioral Responses in Rats

Abstract: Euthanasia in rodents is an ongoing topic of debate due to concerns regarding the aversive nature of gases with anesthetic properties such as carbon dioxide (CO2) and isoflurane. The aim of this study was to expand upon previously published work evaluating the aversiveness of CO2 by introducing an isoflurane treatment group in parallel. Aversion was tested using a forced exposure setup and an aversion-avoidance setup. In the first part of the study, 12 naïve female Sprague–Dawley rats were exposed during four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
(96 reference statements)
2
3
0
Order By: Relevance
“…This suggests that the anesthetic stress and physiological response triggered by isoflurane is more marked than that induced by other inhalant, injectable, and physical methods of euthanasia. The present results are in agreement with what other authors have stated regarding isoflurane as a refinement method for CO 2 [ 52 , 62 ] and affirm that precautions should be taken when deciding to use isoflurane as a sole method for the humane killing of research animals.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This suggests that the anesthetic stress and physiological response triggered by isoflurane is more marked than that induced by other inhalant, injectable, and physical methods of euthanasia. The present results are in agreement with what other authors have stated regarding isoflurane as a refinement method for CO 2 [ 52 , 62 ] and affirm that precautions should be taken when deciding to use isoflurane as a sole method for the humane killing of research animals.…”
Section: Discussionsupporting
confidence: 93%
“…However, studies addressing the mechanism of action of CO 2 and isoflurane, as well as its overdose to induce euthanasia, have shown that both drugs trigger physiological stress and cardiovascular alterations in laboratory rodents [ 26 ]. Although both are considered safe, inexpensive, and effective methods to induce unconsciousness, the results obtained agree with previous findings suggesting that gases with anesthetic properties cause high levels of aversion and stress in mice and rats [ 15 , 52 ].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations